Uncanny x-force (2010), volume 6 ebook - Remender, Rick (Uncanny X-Force (2010), 2013)
Collects Uncanny X-Force #25-29. The end of X-Force? The secret mutant hit squad X-Force has fallen to its lowest point. Its members have sacrificed much, and two have left the team. It's a terrible time for a new, deadlier-than-ever Brotherhood of Evil Mutants to strike at X-Force's heart. This is a Brotherhood like none before. Author: Rick Remender. Illustrator: Phil Noto, Mike McKone, Julian Totino Tedesco. © 2020 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com